Implementation of the Talented Thursday Habituation Program to Encourage Active Participation and Creativity of Elementary School Students - Nurrahmasari, Afrenna Tri; Setiawan, Deni (Universitas Pendidikan Indonesia, 2025)
This study examines the implementation of the Talented Thursday Habituation Program at Jatibarang State Elementary School 03 as an effort to increase the active participation and creativity of grade II students. Using a descriptive qualitative approach, this study describes the process of planning, implementing, and evaluating programs designed to provide a forum for expression through non-academic activities such as art, sports, and drama. Data was collected through observation, interviews, and documentation. The results of the study show that since the implementation of the program in 2022, the active participation of students has increased significantly from 45% of students who actively participated in the talented Thursday habituation program has increased and changed to 80% of students who participated in the talented Thursday habituation program within three months, driven by the active role of teachers, principals, and parental support. Despite obstacles such as limited facilities and time, adjustments to activities and coordination with related parties are able to overcome these obstacles. The findings show that the program is effective in boosting students' confidence and creative expression, while also making a positive contribution to the development of character and non-academic skills. The results of this research are expected to be a practical reference for the development of educational innovations at the elementary level.